Fear thy neighbor [large type] - Michaels, Fern (Wheeler Publishing, a part of Gale, a Cengage Company, 2022)
"At twenty-nine, Alison Marshall is ready to find a place to call home. When she reaches beautiful Palmetto Island, she thinks she may have found it. On a hunch, she contacts the island's only realtor, and learns that an old beach house is on the market. At first, home is everything she hoped it would be. But as days turn into weeks, she uncovers a dark side to this supposedly peaceful haven. The locals have a secret, and once Alison discovers what it is, she faces a stark choice. She can stay and join them--or escape. But leaving brings its own risks, and Alison is starting to wonder if coming to Palmetto Island is the last mistake she'll ever make"--